P550 Early 12-week ultrasound response to treatment, used as a predictor of response at 6 months in Crohn's disease: A prospective cohort study. (16th January 2018) - Halasz, J; Lu, C; Kaplan, G; Tanyingoh, D; Seow, C; Panaccione, R; Devlin, S; Wilson, S; Novak, K
Abstract: Background: Ultrasound (US) is safe and accurate for detecting activity and therapeutic response in Crohn's disease (CD). Early objective assessment may better guide treatment in a treat to target paradigm. The aim of this study is to evaluate 12-week US response to adalimumab (ADA) induction, as a predictor of US, serologic and endoscopic response at 6 months. Methods: Patients with known CD were prospectively recruited from January 1, 2011 to December 31, 2014. Patients with active CD had induction and maintenance therapy with ADA with US and C-reactive protein (CRP) levels measured pre-treatment, at 12 weeks and 6 months. Patients underwent ileocolonoscopy (IC) at baseline. A subset had repeat IC at 6 months. The Simple Ultrasound Score (SUS) was calculated (bowel wall thickness and hyperaemia) at each interval and a Simple Endoscopic Score (SES)/Rutgeert's score for IC when available. Response at 12 weeks was defined by a reduction in SUS or length of disease. Differences between variables at baseline and 6 months were compared using paired sample t test. Features for non-response including presence of strictures or penetrating complications were recorded at baseline. Results: Forty-four patients were included: 64% (28 of 44) females, 36% (16 of 44) male, with mean age of 42 years. Disease distribution was ileal 38% (17 of 44), 55% (24 of 44) ileocolonic and 7% (3 of 44) limited to the colon. All patients exhibited activity on US at baseline, with a mean SUS of 3.14 (out of 4.63). SES was completed for 22 of 44 patients (50%), mean 6.82, Rutgeert's score was completed for 11 of 44 patients (25%), mean 3.27, while 18% (8 of 44) were not amenable to endoscopic scoring and 7% (3 of 44) had no baseline IC. The median baseline CRP was 5.7 mg/l. At 12 weeks, 70% (31 of 44) improved while 30% (13 of 44) had no change or worsened. Responders were evaluated at 6 months for response compared with baseline: SUS and SES were significantly improved, SUS was 3.45 at baseline and 1.84 at 6 months ( p < 0.001) and SES was 6.77 at baseline and 2.50 at 6 months ( p = 0.002). Change in CRP was significant ( p = 0.044); but the change in Rutgeert's score was not ( p = 0.178). No significant difference for any comparison amongst the non-responders was detected. Of the responders, 9 of 31 (29%) exhibited high-risk features at baseline, compared with 5 of 13 (38%) in the non-responders. Conclusions: Sonographic response to ADA induction at 12 weeks significantly increases the likelihood of further response at 6 months. Responders also exhibited a significant reduction in CRP. High-risk features on baseline US may indicate increased likelihood for non-response. Measurement of 12-week US response may help guide early treatment optimisation.